The addressing school bullying: A systematic review (Research, Society and Development, 2024)
School bullying is a complex phenomenon, characterized by intentional, repetitive acts marked by an imbalance of power, which negatively affect the school environment and the emotional health of the victims. The objective of this study was to analyze the characteristics of school bullying, the processes for its identification, prevention, and intervention, as well as Brazilian public policies aimed at addressing this issue. To this end, a systematic literature review was conducted, encompassing analyses of legislation, school practices, and intervention models. The results highlight that Brazil has made significant progress in legislation, such as Law 14.811/24, which criminalizes bullying and cyberbullying, but still faces challenges in the practical implementation of these laws. Intervention models such as Help Teams and the Peer Support System (SAI) prove effective in the early identification and support of victims, promoting a more inclusive and safe school environment. However, there are still gaps in public policies, particularly regarding the adaptation of measures to regional realities and continuous training for the school community. It is concluded that combating bullying requires an integrated approach, combining legislation, specific public policies, and evidence-based school practices. This collective effort is essential to transforming schools into spaces of peaceful coexistence, mutual respect, and the full development of students.